The use of language learning strategies and its role in language learning - Kadiya, Kelimu (2020)
The use of learning strategies in language learning is important in facilitating learners’ language skills and promoting language proficiency. It is believed that learning strategies are special tools for learners to apply in individual learning in order to obtain knowledge and new concepts in language learning (O’Malley & Chamot, 1990). This thesis aims to understand how learners identify and perceive the use of learning strategies in their individual learning (especially in English learning). It also examines what influences the learner’s choice on the strategy use and how the chosen strategies are employed in a learning environment. Ultimately, this study high- lights the perception of learners on the relationship between learning strategy use and learners’ language achievement. Individual interviews were conducted with a total of twelve, both international and domestic, master’s students from the University of Jyväskylä. To address the research questions of the study, the interviews were recorded and the discussions were analyzed with qualitative content analysis through grouping interview answers into key themes. The result revealed that the process of learning English is believed as a continued and holistic process that includes individual goals, learning strategies and its implementation, and the outcomes of strategy use in learning. A variety of learning processes were exposed based on the individual choice of learners. It was also found that learning strategies were selected and employed (consciously and unconsciously) for the purpose of overcoming learning difficulties and improving language skills. The choice of learners on the use of learning strategies was made based on their personalities, interests, learning types, attitudes, etc. The relationship between strategy use and language achievement in learning was described as two types - a linear process and a complex process.